Answer: p^6q^8
Step-by-step explanation:
Answer:
Step-by-step explanation:
the solution is right
x^2-6x-7=0:
x^2-6x-7=0
(add 7 to both sides)
x^2-6x=7
x^2-6x+9=7+9 (the coefficient of x² will be used to divide all sides)for here its 1, it will remain same ,
then we get the coefficient of x, divide it by 2 and square it and add it to both sides
which is like these
x²-6x=7
the coefficient of x is -6
-6/2 = -3, square it (-3)² = 9
then add 9 to both sides
x^2-6x+9=7+9
simplifiy the squares on the left hand side
x²+9 = (x-3)²
(x-3)^2=16
√(x-3)^2 )=±√16
x-3=± 4
x=-3±4
then simplify each sign
x=-3+4 x=-3-4
x=1 x=-7
Answer:
C
Step-by-step explanation:
Solve for x by simplifying both sides of the equation then isolating teh varible.
your answer = - 1/7